[18F]Fluoromisonidazole synthesis method: development and optimization by cartridge purification - Chochevska, Maja; Lazareva, Marija Atanasova; Kolevska, Katerina; Velichkovska, Maja; Koziorowski, Jacek; Ivanovska Janevikj, Emilija; Angelovska, Bistra; Ugrinska, Ana (Walter de Gruyter GmbH, 2023)
[18F]Fluoromisonidazole ([18F]FMISO) as nitroimidazole derivative with 18F radioisotope is a widely known and studied hypoxia marker for PET imaging. A number of automated synthesis modules and purification strategies for production of [18F]FMISO have been described in recent years. The goal of this work was to develop [18F]FMISO synthesis process with Synthera module with solid phase extraction (SPE) Sep-Pak purification cartridges. To adjust the reaction conditions we synthesized [18F]FMISO under different reaction conditions and using various reversed-phase (RP) purification cartridges (HLB light, HLB plus, tC18, C18 environmental, Chromafix PS-RP). The synthesis was performed by nucleophilic substitution of commercial 1-(2′-nitro-1′-imidazolyl)-2-O-tetrahydropyranyl-3-O-toluenesulfonylpropanediol precursor and subsequent acidic hydrolysis. Further, the product mixture was purified by passing through the SPE cartridge. The produced [18F]FMISO was retained on the cartridge, while the impurities passed through the cartridge into a waste. The retained [18F]FMISO was then eluted with small amounts of ethanol in water and eluates were collected in the final product vial. The product sample was subjected to quality control tests, while for waste sample chemical and radiochemical tests were performed. We have developed an efficient synthesis method of [18F]FMISO with cartridge purification with good radiochemical yield (RCY) and high chemical and radiochemical purity in accordance with the Ph. Eur. Monograph for Fluoromisonidazole (18F) injection.